General Mental Health, Quality of Life and Suicide-Related Attitudes Among Kurdish People in Iran - Mofidi, N.; Ghazinour, M.; Araste, M.; Jacobsson, L.; Richter, J. (International journal of social psychiatry, 2008)
Aim: To investigate (1) general mental health, (2) quality of life and (3) suicide-related attitudes in Kurds living in Iranian Kurdistan. Methods: Cross-sectional investigation; cluster random sampling procedure; 1,000 Kurds were randomly selected from 1,000 of 68,000 households in Sannandaj City, Iran; General Health Questionnaire (GHQ-12); Questionnaire on Attitudes Towards Suicide (ATTS). Results: About 27% of the subjects had to be regarded as probably suffering from a psychological disturbance. There was no gender difference regarding the number of `cases'. These possible `cases' were younger than `non-cases'. The most `cases' occurred among the unemployed. An increasing number of experiences related to suicide and the increasing emotional closeness of those experiences was found to be related to an increased probability that the individual would be classified as a `case' according to the GHQ-12 total score. Unmarried individuals more often evaluated their overall quality of life as `moderate' or `bad' compared to married individuals. Unemployed people, self-employed people and housewives formed the groups who most often reported a `very bad' or `bad' quality of life. Conclusions: Kurdish people in Iran are in need of facilities and interventional programmes aiming to improve general mental health.